Ecological and evolutionary drivers of range size in Coenagrion damselflies. (19th September 2014) - Swaegers, J.; Janssens, S. B.; Ferreira, S.; Watts, P. C.; Mergeay, J.; McPeek, M. A.; Stoks, R.
Abstract Geographic range size is a key ecological and evolutionary characteristic of a species, yet the causal basis of variation in range size among species remains largely unresolved. One major reason for this is that several ecological and evolutionary traits may jointly shape species' differences in range size. We here present an integrated study of the contribution of ecological (dispersal capacity, body size and latitudinal position) and macroevolutionary (species' age) traits in shaping variation in species' range size in Coenagrion damselflies. We reconstructed the phylogenetic tree of this genus to account for evolutionary history when assessing the contribution of the ecological traits and to evaluate the role of the macroevolutionary trait (species' age). The genus invaded the Nearctic twice independently from the Palearctic, yet this was not associated with the evolution of larger range sizes or dispersal capacity. Body size and species' age did not explain variation in range size. There is higher flight ability (as measured by wing aspect ratio) at higher latitudes. Species with a larger wing aspect ratio had a larger range size, also after correcting for phylogeny, suggesting a role for dispersal capacity in shaping the species' ranges. More northern species had a larger species' range, consistent with Rapoport's rule, possibly related to niche width. Our results underscore the importance of integrating macroecology and macroevolution when explaining range size variation among species.